Biallelic expansion in RFC1 as a rare cause of Parkinson's disease - Kytövuori Laura; Sipilä Jussi; Doi Hiroshi; Hurme-Niiranen Anri; Siitonen Ari; Koshimizu Eriko; Miyatake Satoko; Matsumoto Naomichi; Tanaka Fumiaki; Majamaa Kari (NATURE PORTFOLIO, 2022)
An intronic expansion (AAGGG)(exp) in the RFC1 gene has recently been shown to cause recessively inherited cerebellar ataxia, neuropathy, and vestibular areflexia syndrome and, furthermore, a few patients with ataxia and parkinsonism have been reported. We investigated 569 Finnish patients with medicated parkinsonism for RFC1 and found biallelic (AAGGG)(exp) in three non-consanguineous patients with clinically confirmed Parkinson's disease without ataxia suggesting that RFC1-related disorders include Parkinson's disease as well.